2002
DOI: 10.1128/aac.46.2.344-349.2002
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Multidrug Resistance-Associated Protein 2 in Intestinal Secretion of Grepafloxacin in Rats

Abstract: We investigated the contribution of multidrug resistance-associated protein 2 (MRP2) to the secretory transport of grepafloxacin and compared its functional role with that of P-glycoprotein (P-gp) by using Sprague-Dawley rats (SDRs) and Eisai hyperbilirubinemic rats (EHBRs), in which MRP2 is hereditarily defective. In intestinal tissue from SDRs mounted in Ussing chambers, the level of transport in the direction from the serosal layer to the mucosal layer was twofold greater than that in the direction from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 19 publications
1
41
0
1
Order By: Relevance
“…MRP2/ Mrp2 appears to play a minor role in intestinal absorption and secretion, especially when Pgp is involved even though they have similar intestinal localization. Furthermore, the oral absorption of grepafloxacin, a Mrp2 and Pgp substrate, was not significantly enhanced by the inhibition of Mrp2; however, biliary excretion was significantly reduced, suggesting differential roles for Pgp and Mrp2 in the intestine and liver (Naruhashi et al, 2002).…”
Section: Saquinavir [Sqv (N-tert-butyl-decahydro-2-[2(r)-hydroxy-4-pmentioning
confidence: 93%
“…MRP2/ Mrp2 appears to play a minor role in intestinal absorption and secretion, especially when Pgp is involved even though they have similar intestinal localization. Furthermore, the oral absorption of grepafloxacin, a Mrp2 and Pgp substrate, was not significantly enhanced by the inhibition of Mrp2; however, biliary excretion was significantly reduced, suggesting differential roles for Pgp and Mrp2 in the intestine and liver (Naruhashi et al, 2002).…”
Section: Saquinavir [Sqv (N-tert-butyl-decahydro-2-[2(r)-hydroxy-4-pmentioning
confidence: 93%
“…Probenecid is a classical competitive inhibitor of organic anions transport also used in the clinical practice to enhance plasma levels of antibiotics. Although nonspeciic, its inhibitory efect on intestinal MRP2 was clearly demonstrated in rats [95] and in Caco-2 cells [90]. Nowadays, more potent and speciic MRP inhibitors like MK5 1 are preferred for characterization of transport speciicity.…”
Section: Post-transcriptional Regulationmentioning
confidence: 99%
“…play a key role in drug absorption (7,8,(13)(14)(15)(16), little is known about the pharmacological and/or toxicological effects of transporter(s) expressed in undifferentiated cells in the small intestine. The aim of the present study is to clarify whether Mrp1, which was reported to be expressed in proliferative cells of crypts in mice, is involved in the intestinal toxicity provoked by MTX in vivo.…”
Section: Although Transporter(s) Expressed In Differentiated Epithelimentioning
confidence: 99%
“…For example, P-glycoprotein (P-gp/ABCB1) and Mrp2 limit the oral bioavailability of certain ß-blockers and new quinolone antibiotics by extruding these drugs into the intestinal tract (13,14). Both Mrp2 and Mrp3/Abcc3 are expressed in the small intestine, and accept MTX as a substrate (15,16).…”
Section: Introductionmentioning
confidence: 99%